2018
DOI: 10.7759/cureus.2306
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Wheat Grass in Thalassemic Children on Regular Blood Transfusion

Abstract: Background: In thalassemia, mutations either in alpha or beta chain synthesis results in low hemoglobin (Hb). Wheatgrass has been used for many years for health purposes. Some reports suggest the beneficial effect of wheatgrass on transfusion requirements. Folic acid is also known to play an important role in several biochemical reactions. In some patients with thalassemia, the supplementation of folic acid is useful.Objective: To evaluate the efficacy and safety of wheatgrass in children with thalassemia rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…In an animal experiment, wheatgrass extract was practically nontoxic at a dosage of 2000 mg/kg [4]. In clinical studies, the use of wheatgrass has not been associated with significant side effects, only nausea and rashes have been reported [5,37]. In our animal experiment, no clinical symptoms were observed in the animals treated with wheatgrass, this supports the safety of this material.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In an animal experiment, wheatgrass extract was practically nontoxic at a dosage of 2000 mg/kg [4]. In clinical studies, the use of wheatgrass has not been associated with significant side effects, only nausea and rashes have been reported [5,37]. In our animal experiment, no clinical symptoms were observed in the animals treated with wheatgrass, this supports the safety of this material.…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, some clinical studies aimed at investigating this supposed effect. In one study, wheatgrass treatment increased the quality of life of children with thalassemia, however there was no reduction in the frequency of blood transfusion requirement [5].…”
Section: Introductionmentioning
confidence: 97%
“…Anti-coagulant Vitamin K [1] Antioxidant, anti-inflammatory action Phenols, amylase Apigenin and quercetin (bioflavonoid) [1,7] Detoxification Chlorophyll [1] Anti-hypertensive, anti-inflammatory Luteolin (bioflavonoid) [1] Metabolism and digestion Cytochrome oxidase, choline, proteins, lipids, threonine [31][32][33][34] Anti-thalassemic Iron [35] Anti-cancer activity Superoxide dismutase, cytochrome oxidase [31] Anti-diabetic Fibers [36] Anti-aging effect Lysine [34] Regeneration of kidney and liver cells Methionine [34] Enhancement of men fertility Arginine [34]…”
Section: Therapeutic Action Chemical Constituent Referencementioning
confidence: 99%
“…Two novel compounds isolated from wheatgrass had the cytotoxic activities against some cancer cell lines (pancreatic, breast, colon, prostate and lung) (Save et al, 2019). It was suggested that wheatgrass might have had an important role in kids with thalassemia receiving chronic blood transfusion (Mutha et al, 2018). The healing effects of wheatgrass juice were presented in a study conducted with type 2 diabetic patients (Shakib et al, 2017).…”
Section: Introductionmentioning
confidence: 99%